11. PERAN UNICEF DALAM MENGATASI PEREKRUTAN TENTARA ANAK DI DARFUR, SUDAN PERIODE 2003-200 - Sihombing, Grace M.S.N; Windiani, Reni; Putranti, Ika Riswanti (Journal of International Relations, 2016)
Darfur is part of Sudan it is divided into three regions which is Western, North, and South Darfur. In early 2003, Darfur has a dark history that began when the two parties, SLA (Sudan Liberation Army) and JEM (Justice and Equality Movement) joined together and formed a movement militarization of politics to carry out a common purpose, which is to fight against the Janjaweed, including to stop political and economic marginalization that occur, and protecting their communities from ethnic cleansing. This kind of conflict often involving children to an armed group. This situation should receive special attention from the international community. For this reason, Government of Sudan should cooperate with UNICEF as the most relevant institutions to address this problem. The aim of this cooperation is to protect the basic rights of children as it has been written in the CRC. The purpose of this study to determine the role of UNICEF in addressing recruitment of child soldiers in Darfur and also to identify cooperation and challenges that UNICEF faced during their duties from period 2003-2005.